FOREIGN EXPERIENCE OF COUNTERACTION OF MONEY LAUNDERING WITH USING THE RISK-BASED APPROACH IN BANKING SECTOR - Уткіна , Олександра (Socio-economic relations in the digital society, 2019)
The international experience of counteracting the legalization (laundering) of criminal proceeds using the risk-based approach are analyzed. Th e supervisory practice of countries, which illustrates the application of a riskbased approach, is presented. The updated FATF Recommendations, their goals and objectives are considered. It has been proven that the national system of fi nancial monitoring in Ukraine has a number of limitations. . In the context of economic, social and political transformations, the ability of banking institutions to identify in a timely and costeffective manner the threats and risks associated with money laundering is urgent and requires detailed study and further improvement. Recommendations that will help eff ectively combat illegal money laundering not only to public authorities but also to the private sector, especially to banking institutions, are provided.